A Patient With Failed Liver Transplantation After the Use of PD-1 Blockade Combined With Lenvaxen - Yin, Jun; Wen, Meng; Cheng, Jun; Hu, Lifen; Yang, Li; Chang, Xiao; Zhou, Zhongsong; Li, Hongbin; Liu, Yan; Li, Jiabin (Frontiers in Medicine, 2022)
Hepatocellular carcinoma (HCC) is a common malignant tumour with a high extent of invasiveness. Its invasion process is closely related to the complex tumour microenvironment and microvascular characteristics. The treatment of HCC is a global problem. In recent years, immune combined targeted therapy has been applied to patients, but a combination therapy program with better effect needs to be explored. The Atezolizumab combined Bevacizumab regimen in phase III clinical trial IMbrave150 was recently approved by the U.S. Federal Drug Administration (FDA) for the treatment of HCC. This program is mostly used for liver malignant tumours that have failed other treatments. Such patients have a poor quality of life and a very limited survival period. The treatment of HCC is a global problem, despite the many current methods. In recent years, immune combined targeted therapy has been applied to patients, but a combination therapy program with better effect needs to be explored. The Atezolizumab combined Bevacizumab regimen in phase III clinical trial IMbrave150 was recently approved by the U.S. Federal Drug Administration (FDA) for the treatment of HCC. This program is mostly used for liver malignant tumours that have failed other treatments. The patient has reached the advanced stage of the disease and is expected to have a limited survival with unsatisfactory antitumor treatment. Patients in the terminal stage, but the overall curative has an unsatisfactory effect, and the survival time of the patients is limited. Therefore, seeking the best plan for combined treatment to improve the patient’s quality of life and survival rate is still one of the most important clinical difficulties. This report describes a 37-year-old male who suffered from HCC repeatedly relapsed after hepatectomy. The patient received transcatheter arterial chemoembolization (TACE), microwave ablation (MWA), targeted therapy, and other combined treatments, but all showed poor treatment effects. The patient received liver transplantation (LT) after receiving PD-1 blockade combined targeted therapy, He eventually died due to severe immune rejection. It is the first case of an allogeneic liver transplantation patient who received PD-1 blockade and Lenvaxen combined therapy. The PD-1 blockade treatment and clinical observations of this case were summarized.